How Do Hospital Staff Cope with Covid-19 at Work? A Phenomenological Study - Febrianto, Wahyu; Indriani, Wiwin; Dewanto, Aryo; Holipah, Holipah (Jurnal Kedokteran Brawijaya, 2021)
The Covid-19 pandemic has brought negative consequences on hospital finances, the mental health of health care workers (HCWs), and even resulted in the deaths of several health workers at Hasta Brata Hospital (HBH). This study aimed to explore the experiences of HBH's staff in dealing with the pandemic in the hospital. This research is qualitative research with a phenomenological approach. Data were collected using in-depth interviews with two of HBH's staff and then followed by the theme analysis. Hospital staff experienced job demands including emotional and physical stress at work, fear of infection, repeated conflicts with patient visitors, different mindsets among staff, increased workload, and feelings of frustration towards people who do not comply with prevention protocols. Fortunately, they had adequate job resources, ranging from the provision of personal protective equipment, nutrition improvement, and regular Covid-19 screening; update knowledge and methods of handling Covid-19; to motivational and spiritual support from HBH leaders. The staff also had strong personal resources so that they could cope with stressful work situations, feel optimistic that they could win against Covid-19, and hoped that the pandemic would end. Spiritual support embodies tawakal, an Islamic concept that gives complete surrender to God after employing maximum effort. The presence of strong job and personal resources has moderated job demands and resulted in work engagement. Tawakal is an added value for personal resources staff who finally realize that Covid-19 cannot be avoided and must be fought before surrendering entirely to God.